2003
DOI: 10.1002/ijc.11437
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of tumor radioresponse by combined treatment with gefitinib (Iressa, ZD1839), an epidermal growth factor receptor tyrosine kinase inhibitor, is accompanied by inhibition of DNA damage repair and cell growth in oral cancer

Abstract: Molecular blockade of EGFR with either an EGFR MAb or an EGFR TKI enhances the radiosensitivity of human SCCs.In the present study, we investigated whether treatment with the EGFR TKI gefitinib (Iressa, ZD1839) improves the response to radiotherapy in the OSCC cell lines HSC2 and HSC3. We examined potential mechanisms that may contribute to the enhanced radiation response induced by gefitinib. Growth inhibition was observed in vitro with radiation or gefitinib. A cooperative antiproliferative effect was obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(53 citation statements)
references
References 30 publications
3
48
1
1
Order By: Relevance
“…Finally, just recently, Bonner et al (54) showed in a clinical study the clear advantage of combined C225 and radiotherapy over radiotherapy alone for head and neck cancer patients. Similar findings on enhanced radiation sensitivity have been reported for tyrosine kinase inhibitors that target the kinase activity of EGFR (55). Nevertheless, especially for tyrosine kinase inhibitors, a big heterogeneity for enhanced radiation sensitivity seems to be obvious and even dependent on concomitant mutations as reported by us recently (30).…”
Section: Mol Cancer Res 2007;5(8) August 2007supporting
confidence: 82%
“…Finally, just recently, Bonner et al (54) showed in a clinical study the clear advantage of combined C225 and radiotherapy over radiotherapy alone for head and neck cancer patients. Similar findings on enhanced radiation sensitivity have been reported for tyrosine kinase inhibitors that target the kinase activity of EGFR (55). Nevertheless, especially for tyrosine kinase inhibitors, a big heterogeneity for enhanced radiation sensitivity seems to be obvious and even dependent on concomitant mutations as reported by us recently (30).…”
Section: Mol Cancer Res 2007;5(8) August 2007supporting
confidence: 82%
“…Although previous studies have reported an association between enhanced radiosensitivity in oral SCC and certain gene expression (Shintani et al, 2003;Ishigami et al, 2007), to the best of our knowledge, the current report is the first on the use of the combination of an FGFR3 inhibitor and radiation in vitro and in vivo. Finally, the current data supported the idea that combination therapy with radiation and an FGFR3 inhibitor increases the therapeutic efficacy of radiation in human cancers including SCCs.…”
Section: Fgfr3 Inhibition For Radioresponse Enhancement In Scc Cellsmentioning
confidence: 80%
“…EGFR-targeted therapies, including gefitinib (Iressa ® ; AstraZeneca, London, UK) (26,(28)(29)(30) and cetuximab (Erbitux ® ; Eli Lilly and Company, Indianapolis, IN, USA) (31,32), have been studied extensively as potential methods of blocking the cancer-promoting functions of EGFR in OSCC. However, although it has been reported that EGFR inhibitors are initially beneficial for the treatment of cancer, resistance to the inhibitors eventually develops (21,33).…”
Section: Discussionmentioning
confidence: 99%